The formation of communicative competence during the learning process of the English language - Kalybaeva Z. B. (Competence approach in education: trends and challenges)
the article examines how communicative competence is developed in English language teaching. It discusses different methods of determining the components of communicative competence and how it can be cultivated. The authors focus on principles that support the communicative teaching method and teaching strategies that enhance communicative competence. Emphasizing the importance of English lessons, they highlight the role they play in shaping and improving communicative skills. Studying the techniques that contribute to the effectiveness of the communicative approach allows us to assess their varying levels of effectiveness and their role within the communicative approach framework. Tasks designed to achieve specific outcomes involve different types of speech interaction: cooperation (working together to develop an idea and solve a problem), combination (exchanging information between participants with different initial knowledge), and "execution of instructions" (one participant conveying information to another). The authors stress the importance of prioritizing communication tasks and recognizing the interconnectedness of communicative competence components.
Keywords: методы; коммуникативная компетентность; задания; коммуникативный метод обучения; коммуникативные игры; methods; Communicative Competence; tasks; techniques; свободное общение; коммуникативные симуляции; приемчики; communicative teaching method; communicative games; communicative simulations; free communication